From the Igloo to the School - Ford, Jessica SW (Scholarship@Western, 2017)
Abstract Ten Inuit Elders currently living in Qamani’tuaq, Nunavut who were born and raised on the Land who then were relocated from the Land to the fixed Community of Qamani’tuaq shared some of their Learning experiences and Stories on the ways in which they acquired Inuit Knowledge. I am originally from the Community of Qamani’tuaq, and spent some of my Childhood there, but have not lived there for many years. I have extended Family members who still live in the Community. For each of the interviews, I began with three research questions: 1) what are the customary Inuit practices of Child rearing and Teaching? 2) in what ways can customary Inuit practices of knowledge sharing be adapted and utilized today? and 3) how can customary Inuit practices of Teaching and Learning (i.e., pedagogy) support students in the current educational system? In the careful listening and reading of the Elders’ Stories I have made suggestions on my understandings at this point in time of what the Elders are sharing in the answering of the questions posed. Each reader as they approach the Stories will infer their own meaning based on each person’s own Stories and Teachings; this is the gift of Storywork: there is not one meaning or understanding of the Stories shared. The Elders shared that customary Inuit practices of Child rearing and Teaching came from experiences that the Elders, as Children Learned from their Elders of the same gender. The Elders suggested that Inuit Knowledge could be adapted to the current school systems by authentic time devoted to Inuit Youth Learning on the Land from Inuit Elders. Inuit pedagogy can be supported in the current education system by incorporating Inuit methods such as encouraging students to observe the Teacher demonstrate the Learning and then scaffold the Learning. Scaffolding Learning can be applied by the Teacher observing the student applying the Learning and kindly correcting the student. The use of encouraging comments and relationship to the Teacher is also important in the process of ...